Evaluating Alef Education's 2024 Olympiad: ACTFL-Based Insights for Madrasah Aliyah - Agustin Janatul Illyah; Nurhadi; Nur Qomari (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to evaluate the extent to which the Olympiad questions correspond to the five key components of the ACTFL (American Council on the Teaching of Foreign Languages) 5C standards: Communication, Cultures, Connections, Comparisons, and Communities. A qualitative library research method was employed, focusing on the collection and analysis of Olympiad test items alongside ACTFL guideline documents. The analysis explored how each question reflects communicative competence, cultural relevance, cross-disciplinary connections, opportunities for language and cultural comparison, and its potential to foster engagement with the broader global community. The findings reveal that the Olympiad questions adequately addressed the Communication and Culture components by promoting interpretive and cultural understanding tasks. However, indicators of interpersonal and presentational communication were less emphasized, indicating a gap in fostering interactive language use. The questions effectively integrated Connections by linking Arabic language learning to interdisciplinary themes such as economics, health, and history, thereby enhancing students’ critical thinking and contextual understanding. Additionally, elements of Comparisons and Communities were implicitly present but lacked explicit engagement with global multicultural perspectives. Overall, the study concludes that the 2024 Alef Education Olympiad provides a valuable model for Arabic language assessment aligned with contemporary global standards, though further refinement is needed to strengthen interpersonal communication and global community integration. It recommends that Arabic language curricula incorporate more authentic, culturally diverse, and communicative tasks to better prepare students for participation in a multilingual and interconnected world. ملخص تهدف هذه الدراسة إلى تقييم مدى توافق أسئلة الأولمبياد مع المكونات الرئيسية الخمسة لمعايير ACTFL (المجلس الأمريكي لتعليم اللغات الأجنبية) 5C: التواصل، والثقافات، والروابط، والمقارنات، والمجتمعات. استُخدمت منهجية بحث مكتبي نوعي، مع التركيز على جمع وتحليل عناصر اختبار الأولمبياد إلى جانب وثائق إرشادات ACTFL. استكشف التحليل كيف يعكس كل سؤال الكفاءة التواصلية، والأهمية الثقافية، والروابط بين التخصصات، وفرص المقارنة اللغوية والثقافية، وإمكانية تعزيز التفاعل مع المجتمع العالمي الأوسع. تكشف النتائج أن أسئلة الأولمبياد تناولت بشكل كافٍ مكوني التواصل والثقافة من خلال تعزيز مهام الفهم التفسيري والثقافي. ومع ذلك، لم يتم التركيز بشكل كافٍ على مؤشرات التواصل بين الأشخاص والعرض التقديمي، مما يشير إلى وجود فجوة في تعزيز الاستخدام التفاعلي للغة. دمجت الأسئلة الروابط بفعالية من خلال ربط تعلم اللغة العربية بمواضيع متعددة التخصصات مثل الاقتصاد والصحة والتاريخ، مما عزز التفكير النقدي لدى الطلاب وفهمهم السياقي. بالإضافة إلى ذلك، كانت عناصر المقارنات والمجتمعات حاضرة ضمنيًا، لكنها افتقرت إلى التفاعل الصريح مع وجهات النظر العالمية متعددة الثقافات. إجمالًا، خلصت الدراسة إلى أن أولمبياد ألف التعليمي لعام ٢٠٢٤ يُقدم نموذجًا قيّمًا لتقييم اللغة العربية يتماشى مع المعايير العالمية المعاصرة، مع ضرورة إجراء المزيد من التحسينات لتعزيز التواصل بين الأفراد والتكامل المجتمعي العالمي. وتوصي الدراسة بأن تتضمن مناهج اللغة العربية مهامًا أكثر أصالة وتنوعًا ثقافيًا وتواصلًا لإعداد الطلاب بشكل أفضل للمشاركة في عالم متعدد اللغات ومترابط.